A fatigue-oriented cost function for optimal individual pitch control of wind turbines. Issue 2 (2020) - Collet, David; Alamir, Mazen; Domenico, Domenico Di; Sabiron, Guillaume
Abstract: In a context of wind power production growth, it is necessary to optimize the levelized cost of energy by maximizing the profit of operating wind turbines, which is defined as the difference between gains (e.g. energy sold) and losses (e.g. operation and maintenance cost). Operation and maintenance cost is intimately related to fatigue damage. However, considering fatigue directly in an optimization needs to be carefully done because its faithful model does not fit standard forms. In this paper, it is first shown that the variance of a signal and its corresponding damage using fatigue theory are nonlinearly related. Therefore, this relationship is used to design a convex cost function approximating fatigue. Preliminary tests suggest promising results regarding the relevance of this formulation in optimizing fatigue trade-off when compared to a family of quadratic cost functions. The proposed formulation allows to directly consider economic parameters in the cost function, limiting thus the sensitivity to parameter tuning.